1994
DOI: 10.1080/02701367.1994.10607611
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Equipment Modification on Children's Self-I and Basketball Shooting Performance

Abstract: The purpose of this study was to examine the effects of modification of basketball size and basket height on shooting performance and self-efficacy of girls and boys 9 to 12 years of age. Subjects (N = 74) completed a self-efficacy questionnaire before and after shooting 10 baskets under four conditions. Shooting conditions were a combination of basketball size (women's or men's) and basket height (10 or 8 ft). Repeated measures analyses of variance indicated that children made more baskets and had higher shoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
1
7

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 19 publications
(30 reference statements)
3
60
1
7
Order By: Relevance
“…The frequency of shot attempts from outside the free throw lane and of lay-ups was not different between the two designs that were studied. This demonstrates that the three-point line with which participants played in the first championship better facilitated the playing and enjoyment of these youth participants in accordance with their capabilities (Piñar et al, 2002(Piñar et al, , 2003Piñar, 2005;Arias et al, 2009), which, according to the bibliography should foster an increase in the perceived competence (Hassandra et al, 2003), in the fun and enjoyment (MacPhail et al, 2008), and in self-efficacy (Bandura, 1977;Chase et al, 1994). The predominance of these motives should allow for greater adherence to mini-basketball, specifically, and to sport participation, in general (Hassandra et al, 2003;Weiss & Williams, 2004;Xiang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of shot attempts from outside the free throw lane and of lay-ups was not different between the two designs that were studied. This demonstrates that the three-point line with which participants played in the first championship better facilitated the playing and enjoyment of these youth participants in accordance with their capabilities (Piñar et al, 2002(Piñar et al, , 2003Piñar, 2005;Arias et al, 2009), which, according to the bibliography should foster an increase in the perceived competence (Hassandra et al, 2003), in the fun and enjoyment (MacPhail et al, 2008), and in self-efficacy (Bandura, 1977;Chase et al, 1994). The predominance of these motives should allow for greater adherence to mini-basketball, specifically, and to sport participation, in general (Hassandra et al, 2003;Weiss & Williams, 2004;Xiang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the first championship, the possibilities to attempt and score a three-point shot were more suitable for the capacities of the players. This would contribute to the increase in the levels of perceived self-efficacy (Bandura, 1977;Chase et al, 1994), which likewise reflects on motivation (Bandura, 1977;Chase, 2001). Piñar (2005), when including a threepoint line in the 3-on-3 modality that was similar to the adult three-point line but at four meters from the hoop, found that the girls achieved a successful three-point basket in 4% of the ball possessions, for a total of nine baskets.…”
Section: Discussionmentioning
confidence: 99%
“…Shortening the pitch should lead to greater efficacy and self-efficacy on the part of bowlers, similar to that found when basket height was modified in basketball. 18 The difference between the numbers of double bounce deliveries in club and county bowling may be explained by the fact that under the club match rules everyone in the fielding side except the wicket keeper bowls, whilst in county games a minimum of five players from the eleven must bowl (and naturally the best bowlers are chosen). Furthermore county bowlers have effectively been selected because they can cope with the current pitch length for their age group, possibly because of better technique, but also perhaps because they are comparatively tall.…”
Section: Discussionmentioning
confidence: 99%
“…Hay pocos estudios en los que se planteen modificaciones reglamentarias en el deporte en general (Andrew, Chow, Knudson, y Tillman, 2003;Dosseville, 2007;Eaves, Hughes, y Lamb, 2008;Giatsis, 2003;Giatsis, y Papadopoulou, 2003;Giatsis, Papadopoulou, Dimitrov, y Likesas, 2003;Hammond, y Hosking, 2005;Hammond, Hosking, y Hole, 1999;Lapresa, Arana, Garzón, Egüén, y Amatria, 2010;Macpherson, Rothman, y Howard, 2006;Meir, Colla, y Milligan, 2001;Pellett, Henschel-Pellett, y Harrison, 1994;Pellett, y Lox, 1997, 1998Ronglan, y Grydeland, 2006;Williams, Hughes, y O´Donoghue, 2005) y en baloncesto en particular (Cárdenas, Piñar, y Baquero, 2001;Chase, Ewing, Lirgg, y George, 1994;Ortega, Castro, y Laporta, 2008;Piñar, 2005;Piñar, Cárdenas, Alarcón, Escobar, y Torre, 2009). …”
unclassified